A Hitherto Unknown Work Ascribed to Mir Damad - Ahmad, Saiyad Nizamuddin (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
A Hitherto Unknown Work Ascribed to Mir Damad